PELATIHAN PEMAHAMAN STRATEGI DAKWA MODERASI BERAGAMA DA’I DAN DA’IYAH BERBAGAI MUI KECEMATAN DI JAKARTA TIMUR - Khairil Ikhsan Siregar; Fidaus Wajdi; Suci Nurpratiwi; Rezza Miftachu Rizqi; Ahmad Reza Maulana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract The approach of religious moderation is crucial in responding to the threats of extremism and religion-based violence in society. An effective strategy for religious moderation in preaching is needed to assist preachers, religious leaders, and the wider community in conveying Islamic values that promote tolerance, peace, and interfaith cooperation. This article aims to outline religious moderation preaching strategies as a guide for disseminating messages that support peace and reject extremism. This study employs a training method consisting of theoretical material delivery and in-depth discussions. The training was held at the East Jakarta office of the Indonesian Ulema Council (MUI) and was attended by preachers from various districts. During the training, materials on religious moderation preaching strategies were presented, followed by intensive discussions between the presenters and participants to deepen their understanding and application of the concepts. The training showed that participants gained new knowledge about religious moderation, particularly in dealing with communities vulnerable to extremism. The participants also experienced an increased understanding of the importance of an inclusive, tolerant, and socially contextual preaching approach in promoting the values of religious moderation. The findings from the training affirm that preaching strategies emphasizing tolerance and interfaith harmony are more effective in preventing extremism compared to rigid approaches. In-depth discussions also helped strengthen participants’ understanding of the importance of considering social and cultural aspects in preaching activities. This study concludes that religious moderation preaching training can provide new insights and effective strategies for preachers and religious leaders in confronting extremism. A balanced and inclusive approach should continue to be developed to foster harmony in culturally and religiously diverse societies. Abstrak Pendekatan moderasi beragama sangat penting dalam merespons ancaman ekstremisme dan kekerasan berbasis agama di tengah masyarakat. Strategi dakwah yang efektif dalam moderasi beragama diperlukan untuk membantu da’i, tokoh agama, serta masyarakat luas menyampaikan nilai-nilai Islam yang mendorong toleransi, perdamaian, dan kerja sama antar agama. Artikel ini bertujuan untuk menjelaskan strategi dakwah moderasi beragama sebagai panduan dalam menyebarluaskan pesan-pesan yang mendukung perdamaian serta menolak ekstremisme. Penelitian ini menggunakan metode pelatihan yang terdiri dari pemberian materi teori dan diskusi mendalam. Pelatihan tersebut dilaksanakan di kantor sekretariat Majelis Ulama Indonesia (MUI) Jakarta Timur dan diikuti oleh da’i serta da’iyah dari berbagai kecamatan. Selama pelatihan, materi mengenai strategi dakwah moderasi beragama disampaikan, diikuti dengan diskusi intensif antara pemateri dan peserta untuk memperdalam pemahaman dan aplikasinya. Pelatihan ini menunjukkan bahwa peserta memperoleh pengetahuan baru terkait moderasi beragama, khususnya dalam menghadapi masyarakat yang rentan terhadap ekstremisme. Para peserta juga mengalami peningkatan pemahaman akan pentingnya pendekatan dakwah yang inklusif, toleran, dan menyesuaikan dengan konteks sosial dalam menyebarkan nilai-nilai moderasi beragama. Temuan dari pelatihan ini menegaskan bahwa strategi dakwah yang menekankan toleransi dan harmoni antar umat beragama lebih efektif dalam menangkal ekstremisme dibandingkan dengan pendekatan yang rigid. Diskusi yang mendalam membantu memperkuat pemahaman peserta mengenai pentingnya mempertimbangkan aspek sosial dan budaya dalam aktivitas dakwah. Studi ini menyimpulkan bahwa pelatihan dakwah moderasi beragama mampu memberikan wawasan baru dan strategi yang efektif bagi da’i dan tokoh agama dalam menghadapi ekstremisme. Pendekatan yang seimbang dan inklusif perlu terus dikembangkan guna menciptakan keharmonisan dalam masyarakat yang beragam secara budaya dan agama.